Physical Child Abuse Potential in Adolescent Girls: Associations with Psychopathology, Maltreatment, and Attitudes toward Child-Bearing. (February 2014) - Pajer, Kathleen A; Gardner, William; Lourie, Andrea; Chang, Chien-Ni; Wang, Wei; Currie, Lisa
Objective: Adolescent mothers are at increased risk of mistreating their children. Intervening before they become pregnant would be an ideal primary prevention strategy. Our goal was to determine whether psychopathology, exposure to maltreatment, preparedness for child-bearing, substance use disorders (SUDs), IQ, race, and socioeconomic status were associated with the potential for child abuse in nonpregnant adolescent girls. Method: The Child Abuse Potential Inventory (CAPI) was administered to 195 nonpregnant girls (aged 15 to 16 years; 54% African American) recruited from the community. Psychiatric diagnoses from a structured interview were used to form 4 groups: conduct disorder (CD), internalizing disorders (INTs; that is, depressive disorder, anxiety disorder, or both), CD + INTs, or no disorder. Exposure to maltreatment was assessed with the Childhood Trauma Questionnaire, and the Childbearing Attitudes Questionnaire measured maternal readiness. Results: CAPI scores were positively correlated with all types of psychopathology, previous exposure to maltreatment, and negative attitudes toward child-bearing. IQ, SUDs, and demographic factors were not associated. Factors associated with child abuse potential interacted in complex ways, but the abuse potential of CD girls was high, regardless of other potentially protective factors. Conclusions: Our study demonstrates that adolescent girls who have CD or INT are at higher risk of perpetrating physical child abuse when they have children. However, the core features of CD may put this group at a particularly high risk, even in the context of possible protective factors. Treatment providers should consider pre-pregnant counselling about healthy mothering behaviours to girls with CD.